Connecting the Enlargement Process with the Europeanization Theory - Teodor Lucian Moga (CES Working Papers, 2010)
Europeanization is one of the theoretical instruments which had a vital influence on candidate countries for EU membership. Due to its aspirations of becoming member of the European Union (EU) and in its attempt to fulfil the Copenhagen criteria, Turkey is trying to comply with the EU acquis communautaire. The aim of this paper is to assess the effects of the Europeanization process on the countries subject to EU enlargement strategy, with a special focus on Turkey, particularly since the country received the EU candidate status in 1999. This paper has been organized in the following way: firstly, it points out how both the traditional Europeanization and the enlargement led Europeanization have been depicted in the work of several important scholars; secondly, by offering a short overview of Turkey's foreign relations vis-à-vis its neighbourhood, especially in the last decade, it examines how the mechanism of Europeanization largely influenced the country's diplomatic culture. Traditionally, Turkey has been attuned to hard security issues and architectures. However, the Turkish foreign policy strategy emphasised in thepast years the Venus side of things in many settings in line with EU requirements.
Keywords: 330; Europeanization theory; the European Union; the enlargement process; foreign policy; international relations